Transmissible Mycobacterium tuberculosis Strains Share Genetic Markers and Immune Phenotypes - Nebenzahl-Guimaraes, Hanna (2017)
Successful transmission of tuberculosis depends on the interplay of human behavior, host immune responses, and Mycobacterium tuberculosis virulence factors. Previous studies have been focused on identifying host risk factors associated with increased transmission, but the contribution of specific genetic variations in mycobacterial strains themselves are still unknown.